(3GdYdd aj SQ GdWHjYIs - (3HdjfGS GdMcjes
(3ChdgG (B:s
(3gPG cJGH GdYdd GdLGeY ddCTjGA CfG HdjfhS UGMH GdCYGLjH GYXe GdUGfY s
(3BNQgG (B:s
(3hEfeG UGQJ Mhd GdTeS hGdbeQ eSJOjQ dGSJOGQI GdTeS JeJ GdebGdI GdKGfjI ef cJGH SQ GdNdjbI s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdKGfjIs
(3GdebGdI GdKGfjI Yf GdBKGQ GdYdhjIs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs